Caracterização da fração de óleo de café extraido de grãos sadios, verdes e preto-verdes, e a influência na adição deste na sensorial de café liofilizado - Colonheze, Ulisses (2015)
The application of roasted coffee oil directly on freeze dried soluble coffee is used to minimize the formation of fine poder which adhere on the glass packaging, which results in a negative visual appearance, as well as contributes to the aromatic impact when opening the packaging. The coffee oil is considered a high cost product obtained from Arabica coffee beans, previosly selected and roasted, by mechanical press. In Brazil the coffee culture and marketing results in the selection of the beans by type of defects and beverage, the volume of exportation works with types of coffee beans with low quantity of defects resulting in a large volume of defective coffee beans trading on the domestic market. Nevertheless, coffees which present defective grains like green, black-green beans present differences in the final flavor of the roasted coffees. The aim of this study was to evaluate the chemical composition of the oils extracted from grains classified as normal, green and black-green, at natural and roasted conditions. The oil was obtained by cold extraction using solvents of different polarities, and yield was calculated as well as its fatty acid composition. The oil of the roasted defective coffee grains was also used to prepare drinks of lyophilized soluble coffee in order to verify if jugdes were able to differenciate the sensory caracteristics of the beverages, in comparison to the product prepared using commercial oil obtained by mechanical pressing. Samples of oil obtained from defective grains showed similar extraction yields compared to hot extraction. Cromatographs of oils of the deffective grains did not showed differences compared to normal grains. In relation to the sensory analysis of the soluble coffee beverages, it was verified that when applying oils of light roasted black-green beans or oils of medium and dark roasted green beans obtained with rapid process, judges had more difficulties to distinguish differences between samples. Economic viability demonstrated that with the actual prices of the coffee beans, the use of defective beans could reduce in 64% the costs of the raw beans.